Gas sensor for ammonia detection based on poly(vinyl alcohol) and polyaniline electrospun - Bittencourt, Jessyka Carolina [UNESP]; Santana Gois, Bruno Henrique de [UNESP]; Rodrigues de Oliveira, Vinicius Jesse [UNESP]; Silva Agostini, Deuber Lincon da [UNESP]; Olivati, Clarissa de Almeida [UNESP] (Wiley-Blackwell, 2019)
In this article, the results of the process and fabrication of ammonia gas sensors are obtained through the production of poly(vinyl alcohol) and polyaniline (PVA/PANI) nanofibers in different concentrations deposited on interdigitated electrodes (IDEs) The results showed good interaction between PVA and PANI, as well as the solvents involved, with good adhesion of the nanofibers in substrate, shown for morphological analysis by scanning electron microscopy (SEM). The good performance of the gas sensor was carried out by direct current measurements. It has been proven that the high surface density, dimensions, and quality of nanofibers are essential parameters for a good response of the ammonia gas sensor. (c) 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47288.
Keywords: ammonia; electrospinning; gas sensors; nanofibers